Influences on Attitudes Regarding COVID-19 Vaccination in Germany - John Paul Fobiwe; Peter Martus; Brian D. Poole; Jamie L. Jensen; Stefanie Joos (Vaccines, 2022)
Trust in institutions and democracy may be a major contributor to the willingness to be vaccinated. We investigated these factors and others with regard to COVID-19 vaccine uptake in Germany. Even though effective vaccination is a major contributor to slowing down the current pandemic, vaccine hesitancy remains a major challenge. To analyze attitudes toward vaccine hesitancy, a web-based cross-sectional survey was used to understand and describe the influences of attitudes about vaccination against COVID-19 in the German population. A descriptive analysis for the entire dataset was carried out, and multiple proportional odds regression, path model, and structural equation modeling (SEM) were subsequently used to analyze any relationship between latent variables and COVID-19 vaccine acceptance. In total, 1092 responses from across Germany were analyzed. SEM modeling revealed that trust in institutions, trust in non-pharmaceutical interventions, and various demographic factors were associated with intent to vaccinate. Descriptive analysis and multiple proportional odds regression confirmed that a history of influenza vaccination and level of satisfaction with democratic institutions were highly predictive (p < 0.05) for COVID-19 vaccine acceptance. Additionally, social determinants of health such as gender, age, number of children in the family, and the degree of satisfaction with life were also predictors (p < 0.05) for COVID-19 vaccine acceptance. Results also demonstrated a significant relationship between receiving the flu vaccine and acceptance of the COVID-19 vaccination. Governments that provide COVID-19 vaccines and control messaging should strive for trust and transparency to maximize vaccine uptake. Government-based vaccine measures should also involve measures to communicate trust in democratic and scientific institutions.